Aspectos anatomopatológicos da leptospirose em cães - Tochetto, Camila (2012)
Leptospirosis is a zoonotic disease caused by spirochetes of the genus Leptospira and it is one of the most important diseases with worldwide distribution. Although leptospirosis is recognized as one of the most commonly reported infectious diseases in dogs, there are no morphological criteria to achieve a definitive diagnosis based only on necropsy lesions. The objective of this study is to establish criteria for the pathological diagnosis of leptospirosis. The necropsy files of the Laboratório de Patologia Veterinária (LPV) of the Universidade Federal de Santa Maria (UFSM) were acessed and all cases diagnosed as leptospirosis between the years of 1965 and 2011 (n=135) were reviewed. Immunohistochemistry for confirmation of definitive diagnosis was performed only in those cases where the kidney tissue was considered viable in quantity and quality (n=79). The positive cases were identified and correspond to the results shown here (n=53). Main necropsy lesions included icterus (79.2%) and hemorrhage (75.5%), mainly in the lungs (56.6%). Gross hepatic (56.6%) and renal (50.9%) changes were frequently found and were characterized mainly by discoloration (respectively 30.2% and 32.1%), accentuation of hepatic lobular pattern (26.4%) and white streaks in the cut surface of kidneys (22.6%). Extrarenal lesions secondary to uremia occurred in half of the cases (50.9%). Enlarged livers (11.3%), and kidneys (9.4%), and rough renal capsular surfaces (3.8%) were less common findings. In the histopathology of the kidneys (n=53), the encountered lesions (98.1%) were almost exclusively acute or subacute (96.2%) and were characterized by varying degrees of tubular nephrosis (86.8%) and non-suppurative interstitial nephritis (60.4%), with evident degenerativeinflammatory dissociation. In the histopathology of the liver (n=42), the encountered lesions (97.6%) consisted mainly of hepatocellular dissociation (78.6%), intracanalicular cholestasis (33.3%) and hepatocellular necrosis (31%). Reactive lesions, such as Kupffer cell hypertrophy, sinusoidal leucocytostasis and inflammatory mononuclear infiltrate within portal triads were observed in several cases (42.8%). In the histopathology of the lung (n=28), alveolar hemorrhage (85.7%) and edema (57.1%) were rather frequent lesions. Neutrophils and macrophages in the alveolar spaces (35.7%) and neutrophils within small pulmonary vessels (17.9%) were also frequent findings. The findings stemming from the current study should serve as an alert for Brazilian veterinary pathologists, since the pathological presentations of canine leptospirosis in this region (Central Region of the State of Rio Grande do Sul, Brazil) did not change in the last 50 years, and is still similar to that described worldwide up to the decade of 1980 s, but rather different from that currently recognized in the United States, Canada and part of West Europe. We recommend that the histopathological criteria for the diagnosis of canine leptospirosis should include the concomitant occurrence of acute or subacute tubulointerstitial nephritis, non specific reactive hepatitis and diffuse alveolar damage, including diffuse alveolar hemorrhage with capillaritis, in dogs which at necropsy had presented icterus, hemorrhage and extrarenal lesions of uremia without splenomegaly.